THE ISLAMIC DECORATIONS ON SAFAVID COPPER COINS BETWEEN THE UNITY AND DIVERSITY IN ITS ILLUSTRATED DECORATIOS ’’SELECTED MODELS FROM FUJAIRAH MUSEUM’’ - Keshk, Shadia Eldesouky Abd ElAziz; Malaka, Mohamed Ahmed (PEOPLE: International Journal of Social Sciences, 2016)
The Museum of Fujairah in the United Arab Emirates contains a collection which includes of 13 copper coins dating to the period of weakness and crisis at the end of Safavid Dynasty, during the reigns of Shah Suleiman "Safi II" (1077-1105 H./1666-1694 C.) and Shah Sultan Hussein I (1105-1135 A.H/1694-1722). The Study aims to discusses the illustrated drawings on these coins throughout the Iranian cities, the theme of the study, and other cities during the Safavid period in general; and this historical period especially which was the beginning of the end of Safavid Daynasty; with the origins of these drawings of the Safavid copper coins "Fulus" through the early Islamic Coins, and through its inclusion on the applied artifacts, such as pottery, textile, metal, wood, carpets, stone and glass during the Islamic Age. The Study shows that the Safavid artists included the decorative elements which represent Sasanian traditions, because the Safavid Dynasty attempted to revive Persian nationalism and regain its previous glory. The Study ends with the results which shows that the decorative elements on theses coins are considered an expansion of the decorative elements which adorned different applied artifacts with drawings on pottery; or carving on wood, stones or marble; or enameling on glass; or printing on textile, that occurred in all Muslim countries since the first century A.H, either in Andalusia, Egypt, Iraq, Levant, and Turkey assuring the unity of decorative elements on coins and different applied artifacts in the frame of Islamic art with the diversity in the decoration methods.